Development of a quadruplex PCR amplicon next generation sequencing assay for detection and differentiation of Bartonella spp. - Bai, Ying; Osikowicz, Lynn M.; Hojgaard, Andrias; Eisen, Rebecca J. (Frontiers in Microbiology, 2023)
The genus Bartonella includes a group of species that are associated with a wide range of mammalian species, including humans. It is challenging to detect all Bartonella species using a single molecular target due to the high genetic diversity. To solve this issue, we developed a quadruplex PCR amplicon sequencing assay using next generation sequencing (NGS) technology for detection and differentiation of Bartonella species. Our goal was to obtain the specific sequences of a minimum of two of the four target genes as confirmation of the identity of a particular Bartonella species using the assay. Four pairs of primers targeting specific regions on gltA, groEL, rpoB, and ssrA were evaluated for their capability of differentiating Bartonella species individually and collectively by performing singular PCR amplicon sequencing and quadruplex PCR amplicon sequencing. Using the quadruplex PCR amplicon sequencing, 24 Bartonella reference species were tested, all of which were successfully differentiated by at least two targets; Bartonella species were accurately identified from the artificially mixed DNA templates developed to simulate coinfections. The limit of detection was determined to be 1fg based on testing a series of 10-fold dilutions of Bartonella DNA. Testing of high DNA concentrations of 19 non-Bartonella species showed high specificity with none misclassified as Bartonella sequences. Finally, the assay was evaluated by testing DNA extracts from field collected body lice (Pediculus humanus humanus) and Norway rats (Rattus norvegicus): B. quintana was detected and confirmed by three targets in the lice; B. tribocorum was detected and confirmed by two targets in the rats. These results demonstrated Bartonella species can be accurately and rapidly detected and differentiated in different tissue types using the quadruplex sequencing assay.